2021
DOI: 10.1108/ijhg-11-2020-0129
|View full text |Cite
|
Sign up to set email alerts
|

Managers' role in supporting resilience in healthcare: a proposed model of how managers contribute to a healthcare system's overall resilience

Abstract: PurposeTo discuss how managers contribute in promoting resilience in healthcare, and to suggest a model of managers' role in supporting resilience and elaborate on how future research and implementation studies can use this to further operationalize the concept and promote healthcare resilience.Design/methodology/approachThe authors first provide an overview of and discuss the main approaches to healthcare resilience and research on management and resilience. Second, the authors provide examples on how manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 39 publications
3
34
0
1
Order By: Relevance
“…Based on our findings, there is also a need for leaders to receive support for managerial tasks to free up their capacity to perform relational leadership, emphasising joint decision-making processes, values, norms, relationships, and communication practices within teams. This appears essential for nurturing organisational resilience [ 43 ] and is still an under researched area within the resilience in healthcare field. Future studies may also include questionaries to detect possible correlations between team leaders’ behaviours and how they are perceived amongst their employees, and safety improvement work [ 37 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, there is also a need for leaders to receive support for managerial tasks to free up their capacity to perform relational leadership, emphasising joint decision-making processes, values, norms, relationships, and communication practices within teams. This appears essential for nurturing organisational resilience [ 43 ] and is still an under researched area within the resilience in healthcare field. Future studies may also include questionaries to detect possible correlations between team leaders’ behaviours and how they are perceived amongst their employees, and safety improvement work [ 37 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resilience perspective is highlighted as valuable for understanding how organizations adapt to challenges, changes and risk, and how organizations succeed in performing their tasks even if exposed to pressure and strain, such as a pandemic . Based on Hollnagel's (2018) description of resilience potentials and Berg and Aase's (2019) suggestions of cognitive and behavioral strategies that characterize resilience in health-care organizations, Ree et al (2021) have proposed a model of managers' role in supporting resilience. They argue that: LHS Managers' role in supporting resilience consists of the strategies managers use to engage people in collaborative and coordinated processes that adapt, enhance or reorganize system functioning, promoting possibilities for learning, growth, development and recovery of the healthcare system to maintain high quality care (Ree et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…6 7 While there are many management approaches, strategies and interventions that have been applied and studied in healthcare, the impact of them on promoting resilience in healthcare has not been explored, particularly at the organisational level. 8 In recent work, Mintzberg states that management and healthcare often have been studied separately in previous research. 9 As such, there is an ongoing demand for a more detailed understanding of management roles and involvement to improve safety and to achieve quality healthcare services.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Accordingly, new studies of management are needed to understand the impact of managers in terms of resilience. 8 However, some studies have identified a connection between management and resilience in healthcare and have suggested there is value in conducting studies to better understand the relationship. 6 11 12 Specifically, 'the higher the skills of leadership, the higher the ability to be resilient and to overcome challenges'.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation